Visualisation des données sur l’offre et la demande de services en soins de longue durée en Ontario: un portrait régional de de l'offre et des besoins réalisé à l'aide de la plateforme dynamique Power-BI de Microsoft (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Visualization of data on the supply and demand for French-language long-term care services in Ontario: A regional snapshot of French-language long-term care supply and demand in Ontario,created using Microsoft's dynamic Power-BI platform (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Tableaux de bord : L’offre et la demande de services de santé en français - Soins de longue durée. (Power-BI, version bêta) - Duong, Patrick; Timony, Patrick E.; Glaude, Normand; Bouchard, Louise (Forces-Santé - Vitrine de données, 2026)
Résumé Ce tableau de bord propose une visualition interactive des données afin d'illustrer le potentiel de l'analyse géographique et de mieux compremdre les besoins des communautés francophones de l'Ontario en matière de soins de longue durée, dans une perspective d'équité et d'accès aux services. Abstract This dashboard provides an interactive visualization of data to illustrate the potential of geographic analysis and to better understand the long-term care needs of Ontario's Francophone communities, with a focus on equity and access to services.

Differences in experiences with episodic virtual care based on language of comfort for healthcare services in New Brunswick, Canada - Gallant, François; Forgues, Éric; Moffitt, Julie; Lavergne, M Ruth (BMC Primary Care, 2026)

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.